Studi karakteristik energi surya untuk pemanenan energi: studi awal di Kota Kendari - La Ode Ahmad Barata; Samhuddin; Rizqi Firti Naryanto; Mera Kartika Delimayanti; La Baride (Piston: Jurnal Teknologi, 2025)
This research aims to evaluate the solar energy characteristics in the Andoonuhu area, Kendari City, Southeast Sulawesi, as a preliminary study for the development of a solar power generation (PLTS). Data collection was conducted using a simulation approach and direct measurements during the period from March to May 2024. The main parameters analyzed include solar radiation intensity, clearness index, zenith, incidence, solar hour angle, and the power output response of the photovoltaic panel SP-50-P36. The study results show that the average daily radiation intensity ranges from 4.5–6.4 kWh/m²/day, with peak energy occurring in May. Analysis of the sun's position on March 23 (equinox) revealed a minimum zenith angle of about 4–5°, indicating near-vertical sunlight conditions relative to the Earth's surface. Solar panels installed at a 15° facing north exhibited relatively small incidence angles during the day, supporting optimal radiation capture performance. Maximum beam radiation was recorded at 12:00 noon, while diffuse radiation contributed more significantly in the morning and evening. The clearness index showed a positive correlation with the solar angle, with optimal values when the elevation angle was above 60°. Panel performance tests revealed a decrease in thermal efficiency due to an increase in module surface temperature up to 49.25°C. This study indicates that the utilization of solar PV energy in Kendari is quite favorable and can be optimized through fixed or tracking system designs. The research provides a technical fundamental data for the development of efficient, sustainable, and adaptive PLTS systems tailored to local radiation characteristics, particularly in the central-eastern region of Indonesia.